Pengembangan Model Pembelajaran Specialist Dialogue Team (SDT) Untuk Meningkatkan Keaktifan dan Hasil Belajar pada Pembelajaran PPKn - Dhari, Diah Putri Wulan (Universitas Negeri Malang, 2021)
This study aimed to produce a cooperative learning model with the Specialist Dialogue Team (SDT) technique to increase the activeness and learning outcomes of students in Pancasila and Civic Education learning. This study used the type of Borg and Gall development research. The results of the study showed that the Specialist Dialogue Team (SDT) learning model was valid and be able to increase the activeness and learning outcomes of students. The validity of the model was known to be the learning expert validation test, obtaining a score of 97.36 and the material expert test was 75 and the lesson plan validation test was 92.18. The activity of students who were originally in the low category became the medium category. The average learning outcomes with post-test scores were higher than pre-test results, Class VIII C with scores from 67 to 77 and Class VIII A in the first meeting from 69 to 78, the second meeting to 84. These results indicated that there has been a significant change between learning outcomes before and after the application of the developed learning model.